INOVASI PEMERINTAH DAERAH MELALUI PEMBANGUNAN ASSESSMENT CENTER DI KOTA BANDUNG - Dede Sri Kartini; Nandang Alamsah Deliarnoor; Herry Wibowo; Rudiana Rudiana (http://jurnal.untirta.ac.id/index.php/JIPAGS, 2017)
Assessment Centre is one of methods which is use a series of test, to examine objectively someone’s capability in various government positions. One of the elements in government stakeholder which need attention to overcome the problem is the configuration of government officer. It consists of the arrangement of institutional governmental bureaucracy, systems and human capital development. In the arrangement of local government civil servant, City of Bandung has been developed Assessment Centre both in methodologically and physically. Following the result of this research, the development of Assessment Centre needed 3 – 5 years to be finished. From its early years, the Assessment Centre was supported by another institution which had been already using Assessment Centre such as Psychology Department in Indonesian Army (Dispiad) and Telkom. This support is no longer needed when the Assessment Centre itself is fully developed. Direct and Indirect preparation is needed to achieve the goals. It also needed support from surrounding ecosystems, such as legality, political will and awareness from participant.Keywords: Government Innovation, Assessment Centre, Competency